Ferroptosis regulators related scoring system by Gaussian finite mixture model to predict prognosis and immunotherapy efficacy in nasopharyngeal carcinoma - Liu, Zijian; He, Jinlan; Hu, Xiaolin (Frontiers in Genetics, 2022)
The role of ferroptosis in tumor progression and metastasis has been demonstrated. Nonetheless, potential biological function of ferroptosis regulatory pattern in nasopharyngeal carcinoma (NPC) remains unknown. Ferroptosis regulatory patterns of NPC samples were evaluated based on 113 ferroptosis regulators and three distinct ferroptosis subtypes were determined. Subtype 1 and subtype 3 were consistent with immune activated phenotype, while subtype 2 was consistent with immune suppressed phenotype. Moreover, a ferroptosis score (FEP score) was constructed to quantify ferroptosis patterns within individual tumors. High FEP score, characterized by immune activation and suppression of mRNAsi and EBV genes, indicated an immune activated tumor microenvironment (TME) phenotype, with better progression free survival (PFS) and lower risk of recurrence and metastasis. Low FEP score, characterized by activation of Wnt and NF-κB signaling pathways and lack of effective immune infiltration, indicated an immune suppressed TME phenotype and poorer survival. High FEP score was also correlated to enhanced response to immunotherapy, and was confirmed to correlate with therapeutic advantages and clinical benefits in an anti-PD-L1 immunotherapy cohort. As ferroptosis played a crucial role in the TME’s diversity, assessing the ferroptosis pattern within individual tumor with FEP score could improve our understanding of TME infiltration characterization and guide more effective immunotherapy strategies.